Sosialisasi Regulasi Emosi pada Siswa SMA Muhammadiyah 1 Surakarta - Adelina Murti Syafiina; Faqih Purnomosidi (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2025)
Adolescence is a crucial stage in individual development, where high school students often face emotional challenges that arise due to physical, psychological and social changes. Unfortunately, many teenagers do not have adequate emotional regulation skills, so they are vulnerable to experiencing difficulties in managing stress, resolving conflicts, or making wise decisions. This limited understanding of emotional regulation can have an impact on mental well-being, triggering impulsive behavior, low motivation to learn, and disruption in interpersonal relationships. Through outreach educational programs, high school students can be given practical knowledge and skills to strengthen emotional regulation abilities. This program is designed to help students recognize their emotions, develop more adaptive management strategies, and improve their ability to deal with everyday stress. With an interactive approach and in line with students' needs, this program is expected to be able to improve emotional well-being while helping students manage their emotions effectively.